2017
DOI: 10.9758/cpn.2017.15.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Low Retinal Dehydrogenase 1 (RALDH1) Level in Prepubertal Boys with Autism Spectrum Disorder: A Possible Link to Dopamine Dysfunction?

Abstract: ObjectiveRetinal dehydrogenase 1 (RALDH1) is a cytosolic enzyme which acts both as a source of retinoic acid (RA) and as a detoxification enzyme. RALDH1 has key functions in the midbrain dopaminergic system, which influences motivation, cognition, and social behavior. Since dopamine has been increasingly linked to autism spectrum disorder (ASD), we asked whether RALDH1 could contribute to the autistic phenotype. Therefore, we investigated for the first time the levels of RALDH1 in autistic patients. To further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Brain regions involved in the control of social behavior include corticolimbic structures and their altered functionality may represent one neural substrate contributing to the social impairments characteristic of ASD (Scott-Van Zeeland et al, 2010; Chevallier et al, 2012; Ameis and Catani, 2015; Supekar et al, 2018). Notably, these regions are subjected to modulation by dopaminergic neurons and it has been suggested that a dysfunction of dopaminergic neurotransmission in the mesocorticolimbic circuit leads to the social deficits observed in ASD (Pavăl et al, 2017): thus, it has been demonstrated that striatal MSNs show enriched expression of genes associated with ASD (Chang et al, 2015) and that ASD-associated mutations affect specific MSN subtypes (Portmann et al, 2014; Rothwell et al, 2014; for a review, see Rothwell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Brain regions involved in the control of social behavior include corticolimbic structures and their altered functionality may represent one neural substrate contributing to the social impairments characteristic of ASD (Scott-Van Zeeland et al, 2010; Chevallier et al, 2012; Ameis and Catani, 2015; Supekar et al, 2018). Notably, these regions are subjected to modulation by dopaminergic neurons and it has been suggested that a dysfunction of dopaminergic neurotransmission in the mesocorticolimbic circuit leads to the social deficits observed in ASD (Pavăl et al, 2017): thus, it has been demonstrated that striatal MSNs show enriched expression of genes associated with ASD (Chang et al, 2015) and that ASD-associated mutations affect specific MSN subtypes (Portmann et al, 2014; Rothwell et al, 2014; for a review, see Rothwell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the DS has been related to behavioral skills belonging to executive functioning, such as analyzing, planning and prioritizing (Seeman, 2010 ; Baronio et al, 2014 ). In line with that, children diagnosed with ASD were found to show deficits in tasks linked to executive functioning, including response/selection, planning/working memory and flexibility (Hellings et al, 2017 ; Paval et al, 2017 ). Moreover, the DS has strongly been linked to social behavior, attentional skills and perception, and motor activity, while development abnormalities in these areas have all been linked to ASD as well (Hellings et al, 2017 ; Paval et al, 2017 ).…”
Section: Correlation Of Neurotransmitters Dysfunction To Asdmentioning
confidence: 76%
“…This would completely exhibit new therapeutic tactic to the clinical control of ASD. Growing evidences suggest that a variety of several neurotransmitter systems such as ACh, 5-HT, DA, GABA, Glu, and HA are implicated in the onset and progression of ASD -along with genetic and environmental factors discussed below- (Shah and Wing, 2006 ; Bacchelli et al, 2015 ; Ellenbroek and Ghiabi, 2015 ; Wang et al, 2015 ; Chen et al, 2017 ; Hellings et al, 2017 ; Hellmer and Nystrom, 2017 ; Naaijen et al, 2017 ; Nakai et al, 2017 ; Paval, 2017 ; Paval et al, 2017 ; Figure 1 ).…”
Section: Correlation Of Neurotransmitters Dysfunction To Asdmentioning
confidence: 99%
See 2 more Smart Citations